Biostratigraphy of the late Early Pleistocene (Eopleistocene) of the Southern Fore-Urals region (Russia). (20th April 2019) - Yakovlev, Anatoly; Danukalova, Guzel; Kurmanov, Ravil; Osipova, Eugenija
Abstract: A summary of published and unpublished data on the stratigraphy of the late Early Pleistocene (Eopleistocene) of the Southern Urals region is presented in this paper. The summary follows previous reviews about the characteristics of the Pleistocene deposits of the easternmost part of Europe. The improvement and unification of the regional Quaternary stratigraphic scheme is the main aim of these investigations. In this paper we describe deposits of different origin, which constitute the regional stratigraphic units (Tyulyan, Raevka, Udryak, Khlebodarovka, Dombarovka, Blagovar and Oktyabrsky Horizons), are characterized. During the late Early Pleistocene (Eopleistocene), the Southern Fore-Urals region was characterized by continental climate conditions and by four phases of incisions of the hydrographic network that were related to regional uplift, as well as to the lowering of the base level and the subsequent regression of the Late Akchagylian Sea. Fossil molluscs, ostracods, mammals and pollen are used for the reconstruction of the palaeoenvironmental conditions and the biostratigraphical positions of the main localities. During Raevka, Khlebodarovka and Blagovar times, the climate was cool, and forest-steppe landscapes with prevalent open spaces existed. The climate during the Tyulyan, Udryak, and Dombarovka and Oktyabrsky times was warm, and during these periods, the areas of deciduous and coniferous forests expanded in the forest-steppes. The molluscan fauna of the Early Eopleistocene was a transitional fauna from the Pliocene to the Quaternary because the wet and warm climate, which was favourable to the Pliocene mollusc species, continued in the Southern Fore-Urals during the Early Eopleistocene. The mammalian assemblages are the basis for the biostratigraphical subdivision. The deposits are biostratigraphically correlated to the Lower Eopleistocene on the basis of the appearance of the first unrooted voles Allophaiomys and Prolagurus together with late species of the Mimomys genus. At the end of the Eopleistocene, the unrooted voles Terricola and Lagurina were numerous, the first Microtus appeared, late species of Mimomys were not numerous, and Archidiskodon trogontherii appeared in the mammal faunas of the region. The small mammals of the Tyulyan and Udryak times represent the Odessa faunal assemblage. The mammal fauna of the Oktyabrsky time corresponds to the Tiraspol faunal assemblage. The units are correlated with the Upper Villafranchian – Galerian stages interval in the Western European stratigraphical timescale.